2017
DOI: 10.1001/jamaoto.2017.0238
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Intravenous Acetaminophen vs Placebo for Endoscopic Sinus Surgery and Postoperative Pain

Abstract: clinicaltrials.gov Identifier: NCT01608308.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
0
22
1
Order By: Relevance
“…No other systematic review or meta‐analysis was found pertaining to perioperative and postoperative analgesic use for endoscopic sinus surgeries. Thirty‐two studies met the inclusion criteria for this project: all of the included studies were randomized, controlled trials (RCTs). Using the Cochrane Bias tool, we judged 4 studies to be at high risk, 21 to be at moderate risk, 6 to be at low risk, and 1 to be at unclear risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No other systematic review or meta‐analysis was found pertaining to perioperative and postoperative analgesic use for endoscopic sinus surgeries. Thirty‐two studies met the inclusion criteria for this project: all of the included studies were randomized, controlled trials (RCTs). Using the Cochrane Bias tool, we judged 4 studies to be at high risk, 21 to be at moderate risk, 6 to be at low risk, and 1 to be at unclear risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, appropriate adherence and utilization are crucial factors in optimizing the effectiveness of regimens. Aggressive administration of acetaminophen in the preoperative period was noted to be a major factor influencing patient analgesia, a consideration that should be discussed with the physician anesthesiologist as part of an anesthesia care plan before induction. Furthermore, several studies reported significant value in scheduling acetaminophen administration for postoperative outpatient pain control, rather than instructing patients to take this medication on an as‐needed basis.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the subset of patients requiring additional pain management would also exhibit distinctive SNOT‐22 domain scores. Identifying this cohort of patients before surgery would allow for development of a personalized pain control plan or utilization of perioperative multimodal analgesic therapy . In the present study, we investigated the predictive value of baseline and follow‐up SNOT‐22 scores of patients who underwent ESS on their likelihood of requiring additional opioid prescriptions (AOPs) after surgery.…”
mentioning
confidence: 99%
“…Similar results have been shown in the study after CABG surgery, in which about 4.7 mg less of Morphine was required during a 1-24h after starting interventions with the IVA (6). Cattabriga et al, reported a significant reduction in pain but not cumulative opioid consumption after cardiac surgery (19); other trials also report improved pain scores without a reduction in opioid consumption (7,8). Our results are consistent with those reported by Jelacic et al recently indicated that IVA significantly reduction 24-hour postoperative opioid consumption (11).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found to be safe and effective for reducing pain and opioids consumption (5). Studies have shown that Acetaminophen can be administered through different routes to control post-operative pain (6,7). Geoffrey et al demonstrated there were no differences in side effects such as nausea, Itching, dizziness and drowsiness among Oral Acetaminophen (OA) and Intravenous Acetaminophen (IVA) (8).…”
Section: Introductionmentioning
confidence: 99%